Design of Mixed‐Metal Silver Decamolybdate Nanostructures for High Specific Energies at High Power Density. Issue 32 (17th May 2016) - Kumar, Vipin; Matz, Sebastian; Hoogestraat, Dirk; Bhavanasi, Venkateswarlu; Parida, Kaushik; Al‐Shamery, Katharina; Lee, Pooi See
Abstract : Mixed‐metal molybdates are interesting host materials for ion‐insertion electrodes due to their versatile crystal chemistry, which confers a highway for the conduction of electrons as well as ions. Silver decamolybdate in triclinic crystal structure (T‐Ag6 Mo10 O33 ) consists of layers of MoO6 octahedra separated by arrays of silver ions that are able to store a high amount of charges.